TARI KANCAH DI NAGARI CUBADAK, TANAH DATAR, SUMATERA BARAT: ANALISIS PERUBAHAN TEKSTUAL DAN SIGNIFIKANSINYA DALAM BUDAYA - Maghfira, Miftahul; Hardi, Hardi; Yarlis, Yarlis (Laga-Laga : Jurnal Seni Pertunjukan, 2023)
The research titled "Kancah Dance in the Life of the Nagari Cubadak Lima Kaum Community, Tanah Datar Regency, West Sumatra Province: A Study of Textual Changes" aims to explore the forms of Kancah Dance in the life of the community in Nagari Cubadak Lima Kaum, Tanah Datar Regency, West Sumatra Province, with a focus on textual change analysis. The research method employed is qualitative and analytical descriptive. Data were obtained through literature reviews and field studies, involving observation and in-depth interviews with five informants. The study applies the theories of change and textual proposed by Sjafri Sairin and Y. Sumandiyo Hadi. The expected results will provide a deeper understanding of the evolution of Kancah Dance and changes in the textual context within the community. This research contributes to the performing arts literature and enriches the understanding of how traditional arts continue to evolve and adapt to changing times.